Snake Venoms in Cancer Therapy: Past, Present and Future - Li Li; Jianzhong Huang; Yao Lin (Toxins, 2018)
Cancer is one of the leading causes of morbidity and mortality worldwide, and the discovery of new drugs for cancer therapy is one of the most important objectives for the pharmaceutical industry. Snake venoms are complex mixtures containing different peptides, proteins, enzymes, carbohydrates and other bioactive molecules, which are secreted by the snake in the predation or defending against threats. Understanding the snake venoms may turn the toxins into a valuable source of new lead compounds in drug discovery. Captopril, the first angiotensin-converting enzyme inhibitor approved in 1981 by FDA, was designed based on the structure of a peptide isolated from the snake venom. The earliest reports about snake venoms used in cancer treatments appeared in the 1930s. Since then, numerous studies on the activities, isolations, purifications and structure elucidations of the components from snake venoms were published. The comprehensive structural and functional investigations of snake venoms would contribute to the development of novel anti-cancer drugs. Our review will focus on the past, present and the future of the studies on snake venoms in cancer target therapy.